Screening differentially expressed proteins of coronary heart disease with congenital cold syndrome based on tandem mass tag (TMT) technology. Issue 1 (1st January 2021) - Xie, Tingting; Guo, Jiajuan; Jiang, Yanshu; Li, Lijie; Jiang, Lihong; Wei, Yan
ABSTRACT: In our previous studies, we discovered the congenital cold syndrome (CCS), which is characterized by 'qi deficiency and qi stagnation, mixed cold and heat.' And there is a type of syndrome with special incidence characteristic. However, the diagnosis of CCS still lacks an objective basis. In this study, we performed Tandem Mass Tag (TMT) based on quantitative proteomics technology to screen the significantly differentially expressed proteins (DEPs) in serum of patients with coronary heart disease (CHD) patients with CCS, patients with heart and kidney yang deficiency, and healthy people. A total of 22 DEPs (nine upregulated and 13 downregulated) were identified between patients with CCS and healthy subjects. Next, we performed GO and KEGG pathway enrichment analysis, we found the primary functions of DEPs of CCS were binding, catalytic activity, and molecular function regulator. These DEPs were mainly involved in important biological processes, such as cellular process, response to stimulus, localization, metabolic process, and biological regulation. The KEGG analysis revealed that the DEPs showed significant changes in fructose and mannose metabolism, Pentose phosphate pathway, and Arrhythmogenic right ventricular cardiomyopathy. After parallel reaction monitoring (PRM) verification, four upregulated target proteins (ALDOA, PCYOX1, Crisp3 and IGLV4-69) and three downregulated proteins (ALDOC, ADAMTSL-2 and C3) were accurately identified. These proteins were mainly related to immune response and glucose metabolism. These DEPs could be the marker proteins of coronary heart disease with CCS. This findings help to reveal the pathogenesis of CHD with CCS and provide potential therapeutic targets. GraphiCal abstract: uf0001